(untitled) (VETERINARIA, 2020)
Sheep production in Bosnia and Herzegovina is one of the most promising branches of livestock production, and all measures should be taken in the direction of its modernization. Increasing Pramenka’s dairy skills is one of the quality directions with expected positive results. Awassi, as a highly adaptable and dairy breed, has all the prerequisites to be a strategic meliorator towards the creation of high-dairy F1 generation with pramenka. Analyzing the production characteristics of these two breeds, geographic and socio-economic characteristics in BiH, and referring to positive experiences from Macedonia, the need of directing the sheep strategy in the aforementioned direction becomes clear. Also, it is an imperative to start a pilot project in BiH aimed at exploring the significance of enrichment of Pramenka with Awassi rams.